Library Management System - Tong, Yhee Renn; Nazri Bin Mohd Nawi (Applied Information Technology And Computer Science, 2022)
Library Management System is designed to manage and maintain the records of library. Some of the library does not implement computerized library management system and still applying manual form to manage data. The main objective of the system will be overcome the problem by introducing the system to provide a better way in the library to address the problems effectively. Waterfall development model is used to develop the library management system with the purpose of ensuring the system undergo an analysis before starting to develop. The library that use the computerized library management system would provide efficiency to both the administrator and the users of library. The system would help the administrator to carry out operations easily as it simplified the processes. The improvement on the library system will overturn the expectations of library users and administrator as the improvement would bring both the challenges and opportunities to the library.